2021
DOI: 10.3390/jmse9020180
|View full text |Cite
|
Sign up to set email alerts
|

Improving Near Miss Detection in Maritime Traffic in the Northern Baltic Sea from AIS Data

Abstract: Ship collision is the most common type of accident in the Northern Baltic Sea, posing a risk to the safety of maritime transportation. Near miss detection from automatic identification system (AIS) data provides insight into maritime transportation safety. Collision risk always triggers a ship to maneuver for safe passing. Some frenetic rudder actions occur at the last moment before ship collision. However, the relationship between ship behavior and collision risk is not fully clarified. Therefore, this work p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Review papers by Szlapczynski and Szlapczynska (2017) present the rationale of the most influential models/methods. Du et al (2021) summarized the typical ship domains and its applications as shown in Fig. 1.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Review papers by Szlapczynski and Szlapczynska (2017) present the rationale of the most influential models/methods. Du et al (2021) summarized the typical ship domains and its applications as shown in Fig. 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development and application of innovative statistical and analytics methods to provide novel insights into collision risk assessment at sea are essential and meaningful (e.g., Zhang et al, 2020;Mannering et al, 2020;Zeng et al, 2016;Antão and Soares, 2019). The research over the last two decades mainly focuses on (a) safety domain quantification (e.g., Lei et al, 2021;Szlapczynski et al, 2018a), (b) conflict scenarios detection (e.g., Zhang et al, 2015a;Zhang et al, 2021a;Zhang et al, 2021b;Du et al, 2021), and (c) collision risk evaluation (e.g., Rawson and Brito, 2021;Zhang et al, 2020;Huang and Van Gelder, 2020a). Mostly these approaches qualify risks by evaluating the geographical positioning of ships and the difficulty of avoiding collisions to present spatial-temporal maps to demonstrate collision risk levels, which meet the requirements for the evaluation of ship-ship collision risk or ship-to-offshore structures contact risk (Goerlandt and Montewka, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of the global economy, maritime trade has become more frequent in recent years, and maritime traffic demand is accordingly increasing, causing significant changes in ship traffic [1]. The changes to ship traffic are mainly reflected in the increasing volume and complexity of ship traffic, leading to an obvious increase in the probability of collisions, which have a serious impact on maritime traffic safety and cause serious loss of life, property, and environment [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…An Automatic Identification System (AIS) provides rich information including ship type, position, course over ground (COG) speed over ground (SOG) [25], etc. AIS has been applied in a series of studies on data fusion, abnormal detection, and risk detection [26][27][28]. Inspired by this, a few studies are attempting to mine AIS data for MASS designing testing scenarios.…”
Section: Introductionmentioning
confidence: 99%